2021
DOI: 10.1007/s11665-021-06207-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Processing Routes on the Microstructure and Thermoelectric Properties of Half-Heusler TiFe0.5Ni0.5Sb1−xSnx (x = 0, 0.05, 0.1, 0.2) Alloys

Abstract: Sn-doped TiFe 0.5 Ni 0.5 Sb 12x Sn x (x = 0, 0.05, 0.1, 0.2) were synthesized by vacuum arc melting (VAM). In addition to the half-Heusler phase, secondary phases of Fe-Sb-rich compound and Ti-rich compounds were obtained after VAM. The alloys were then subjected to ball milling for 1 h and 5 h. Ball milling for 1h led to microcrystalline grains, while that for 5 h led to nanocrystalline grains. Ball milling followed by spark plasma sintering (SPS) at 1173 K led to significant reduction in size of secondary ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…1(c). Additionally, the optimum zT of the newly discovered ZrNi(In,Sb) compounds is comparable with that of other double HH systems 21,[35][36][37] (Fig. S5 †), demonstrating that ZrNi(In,Sb) compounds enrich the HH families and can potentially be applied in electricity generation.…”
Section: Thermal Transport Propertiesmentioning
confidence: 52%
“…1(c). Additionally, the optimum zT of the newly discovered ZrNi(In,Sb) compounds is comparable with that of other double HH systems 21,[35][36][37] (Fig. S5 †), demonstrating that ZrNi(In,Sb) compounds enrich the HH families and can potentially be applied in electricity generation.…”
Section: Thermal Transport Propertiesmentioning
confidence: 52%
“…However, the line spectra along these precipitates in the as-cast x = 0.40 sample in Figure S3b show that some oxidation may have occurred during the arc melting phase despite the measures taken to reduce oxidation. It should be noted that the high affinity of the Zr atom for oxygen is well known and widely used in the synthesis of oxide-free alloys, and that could be related to the frequent detection of Ti and Zr precipitates in Ti- and Zr-based hHs. ,,, The stoichiometric imbalance resulting from the Zr deficit in the matrix after oxidation could favor the formation of the observed Zr precipitates and Sb-based impurity phases, revealing a critical challenge in the synthesis of homogeneous Zr-based half-Heusler materials. However, amounts of the impurities in the pristine and the x = 0.45 and 0.40 samples are below the spatial detection limit of XRD, so they do not cause significant changes in thermoelectric properties due to their sparse distribution and small amount, as found in previous half-Heusler systems. , …”
Section: Resultsmentioning
confidence: 99%
“…In addition to increasing n and m * and suppressing κ latt , Co doping converted the pristine TiFe 0.50 Ni 0.50 Sb into more efficient p-type TiFe 0.50 Co 0.15 Ni 0.35 Sb and n-type TiFe 0.3 Co 0.2 Ni 0.5 Sb compositions, which were subsequently doped with Hf to achieve higher zT s of 0.65 in n-type Ti 0.8 Hf 0.2 Fe 0.3 Co 0.2 Ni 0.5 Sb and 0.85 in p-type Ti 0.8 Hf 0.2 Fe 0.5 Co 0.15 Ni 0.35 Sb . Even more intriguingly, new research has revealed that altering the Fe/Ni atomic ratio also allows TiFe 0.50 Ni 0.50 Sb to be tuned intrinsically into the p- and n-types with competing zT s, stemming from improved n , suppressed κ latt , and most importantly, noticeably higher m *. ,, Consequently, zT s of 0.5 and 0.7 at 973 K were obtained for n-type TiFe 0.4 Ni 0.6 Sb and p-type TiFe 0.6 Ni 0.4 Sb, respectively, and increased to 0.7 and 1 at 973 K after subsequent Hf doping, representing the highest zT s among DhH materials . Therefore, this presents an avenue for producing low-cost n- and p-type DhHs with strong performance tunability from a common parent compound.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, substituting Ni and Fe instead of Co in TiCoSb to form TiFe 0.5 Ni 0.5 Sb double half-Heusler exhibited roughly 35% lower thermal conductivity. 28 The κ l value was lowered to 1.95 W/(m•K) in the Ti 1.6 Hf 0.4 FeNiSn 1.7 Sb 0.3 double HH alloy. 29 Similarly, a low κ l value (in HH alloys) of 2.00 W/(m•K) was observed in triple HH Mg 2 VNi 3 Sb 3 .…”
Section: Introductionmentioning
confidence: 99%